2005
DOI: 10.1016/j.clinph.2005.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Increase in 20–50Hz (gamma frequencies) power spectrum and synchronization after chronic vagal nerve stimulation

Abstract: Objective: Though vagus nerve stimulation (VNS) is an important option in pharmacoresistant epilepsy, its mechanism of action remains unclear. The observation that VNS desynchronised the EEG activity in animals suggested that this mechanism could be involved in VNS antiepileptic effects in humans. Indeed VNS decreases spiking bursts, whereas its effects on the EEG background remain uncertain. The objective of the present study is to investigate how VNS affects local and inter regional syncronization in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 56 publications
(64 reference statements)
4
45
0
Order By: Relevance
“…Theta band connectivity has also been proposed as an early diagnostic test for epilepsy (Douw et al 2010a), and pathologically elevated theta connectivity has related to greater seizure frequency (Douw et al 2010b). Finally, a treatment of epilepsy, vagus nerve stimulation, has previously been shown to increase and decrease gamma and theta band connectivity, respectively, underscoring the potential relevance of our findings for seizure control (Marrosu et al 2005).…”
Section: Discussionmentioning
confidence: 84%
“…Theta band connectivity has also been proposed as an early diagnostic test for epilepsy (Douw et al 2010a), and pathologically elevated theta connectivity has related to greater seizure frequency (Douw et al 2010b). Finally, a treatment of epilepsy, vagus nerve stimulation, has previously been shown to increase and decrease gamma and theta band connectivity, respectively, underscoring the potential relevance of our findings for seizure control (Marrosu et al 2005).…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, it may be unambiguously stated that occurring potentials correspond to the commonly accepted standards. In the case of humans, presently ac cepted standardization (Salansky et al 1998, Aurlien et al 1999, Finnerup et al 1999, Nishida 1999, Razoumnikova 2003, Rowan et al 2004, Marrosu et al 2005, LeVan et al 2006 allows to determine the neurophysiological state of a patient. The research is so advanced that, as it is suggested by Velis (2005), it is possible to determine the predispositions for a job performance on the basis of elec troencephalogram.…”
Section: Determination Of a Normal Reaction Of The Cerebral Cortex Bimentioning
confidence: 99%
“…CSF aspartate level, an excitatory neurotransmitter, has also been shown to decrease significantly in chronic VNS. On an electrical point of view, EEG studies have proven cortical synchronization or desynchronization depending on stimulation frequency and intensity, explaining the importance of rigorous stimulation parameters in VNS (Marrosu 2005).…”
Section: Rationale Of Vns In Refractory Epilepsymentioning
confidence: 99%